Potensi kemopreventif fraksi n-heksan biji kebiul (Caesalpinia bonduc (L) Roxb.) Bengkulu pada chorioallantoic membrane yang diinduksi bFGF - Hayati , Risda; Nadia, Nadia; Karini , Amey Putri; Shavitry, Ayyu; Romdani, Ayu Nadiyah Permatasari; Wulandari, Septi (Journal of Pharmaceutical and Sciences, 2023)
Cancer is the growth or swelling of a mass of abnormal, uncontrolled and malignant cells. With the formation of these blood vessels, antiangiogenesis is needed because without a blood supply, cancer cells will die. The kebiul seed plant (Caesalpinia bonduc (L) Roxb.) contains secondary metabolites as anticancer. This research uses experimental methods, namely making N-Hexane extracts and fractions, Phytochemical Tests, and Antiangiogenesis Tests. The yield of kebiul seeds was 13.608%. In the phytochemical test, the n-hexane fraction of kebiul seeds gave positive results for alkaloids, flavonoids, triterpenoids and tannins. In the blank paper disc group, paper discs with DMSO solvent and paper discs induced by bFGF the average score was 0 (not active). The N-Hexane fraction with a concentration of 02 mg/ml is the most active and has the greatest and best antiangiogenesis effect with an average score of 1.66 (Good), at a concentration of 0.1 mg/ml with an average score of 1.33 (good) and at a concentration of 0.05 mg/ml with an average score of 0.83 (weak). Macroscopic observations showed that kebiul seed extract inhibited the growth of new blood vessels in the bFGF-induced CAM of chicken embryos depending on the concentration given.